Effect of Octreotide in stopping post surgical chyle leak in neck Dissection-A systematic review - Surabhi Magoo; Kalyani Bhate; S.N. Santhosh kumar; Pradnya Kakodkar; Monica Gajul; Santoshkumar Mastud (Elsevier, 2022)
Objective: Neck dissection causes an unusual and challenging complication called Chyle Leak. Octreotide, a long-acting somatostatin analogue, is one way Chyle Leak can be managed faster and effectively. The objective of the review was to evaluate the efficiency of Octreotide in stopping post surgical Chyle Leak in neck dissection. Methods: Three electronic database and manual search was undertaken to identify the literature. All the published articles, which included data about Octreotide used to stop post-surgical Chyle leak in neck dissection, published in the English language between January 1, 2010 to May 31, 2022 were included. Joanna Briggs critical assessment tool was used to assess the included studies. Results: Preliminary screening of 206 studies from data sources and ten from additional sources was done. After necessary exclusion, ten studies were included for qualitative synthesis. The data included 65 patients with neck dissections followed by Chyle leak postoperatively. Chyle leak was presented from 0-8th POD (range of 150 ml-2500 ml). 100mcg-eight hourly subcutaneously was given in maximum studies for 2-14 days. A gradual reduction in chyle leak started 2-4 days after the administration. The chyle leak completely resolved within 2-11 days in the majority of cases with conservative treatment and Octreotide. Conclusion: Octreotide Therapy with primary treatment is an effective way of stopping Chyle Leak in Neck Dissection. However, well-designed and robust randomized controlled studies are needed to confirm the results in the future.